Efect of Cosubstrate Ratio and Temperature on Sewage Sludge and Agro‐industrial Fruit and Vegetable Waste Anaerobic Co‐digestion (2025)
The continuous increase in the generation of organic waste and sewage sludge, coupled with rising global energy demands, calls for sustainable and integrated waste-to-energy strategies. Anaerobic co-digestion (ACoD) emerges as a promising solution, enhancing energy recovery while ensuring environmental protection. This study investigates the ACoD of sewages ludge (SS) and the agro-industrial fruit and vegetable waste (AFVW) under diferent substrate ratios 50/50, 60/40, and 70/30) and temperature conditions (ambient and mesophilic at 35 °C). The objective was to optimize methane yield, organic matter degradation, and pathogen removal. The highest methane production (542.88 mL CH4/g VS) occurred in the 70/30 mix under mesophilic conditions, associated with improved biodegradability and a favorable C/N ratio. Volatile solids and total organic carbon removal were enhanced without signs of ammonia inhibition. Importantly, signifcant reductions in Escherichia coli, Salmonella spp., and helminth eggs were achieved, meeting safety thresholds for agricultural biosolids reuse. Among six kinetic models, the Cone model best ftted the experimental data (R2>0.98), validating its predictive potential for ACoD performance. The 70/30 mix under ambient conditions also exhibited competitive results, reinforcing the feasibility of low-energy-input systems in decentralized contexts. Overall, this work highlights the potential of ACoD to simultaneously address organic waste management, renewable energy generation, and pathogen control, supporting the transition toward a circular economy and the achievement of Sustainable Development Goals.